(3eYQaI GdbQGA GdcHGQ Ydi GdWHbGJ hGdEYUGQs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOI GdPjf GUWai CeG HYO agPG cJGH ajg eYQaI GdeTghQjf ef GdbQGA GdCYjGf s
(3BNQgG (B:s
(3ef JQLeI TeS GdOjf CHj YHO Gddg eMeO Hf GHQGgje GdRfLjdi GdOeTbi GdMfai (B: (3hcJH GdNW GdefShH hHQY ai GdTQhW , hMLH bGVi GdbVGI fLe GdOjf LjO GdeTGQcI ai Gdafhf s
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda (B: (3hYdjgG NWg HPdcs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs